A Parametric Approach to Shape Field-Relevant Blast Wave Profiles in Compressed-Gas-Driven Shock Tube - Sundaramurthy, Aravind; Chandra, Namas (Frontiers in Neurology, 2014)
Detonation of a high explosive produces shock-blast wave, shrapnel, and gaseous products. While direct exposure to blast is a concern near the epicenter, shock-blast can affect subjects even at farther distances, which is termed as primary blast injury, which is the theme of this work. The shock-blast profile is characterized with blast overpressure, positive time duration, and impulse as shock-blast wave parameters (SWPs). These parameters in turn are a function of field factors, such as the strength of high explosive and the distance of the human subjects from the epicenter. The shape and magnitude of the profile determine the severity of injury to the subjects. As shown in some of our recent works (Chandra et al., 2011;Sundaramurthy et al., 2012;Skotak et al., 2013), the profile not only determines the survival of the animal but also the acute and chronic biomechanical injuries along with the following bio-chemical sequelae. It is extremely important to carefully design and operate the shock tube to produce field relevant SWPs. Furthermore, it is vital to identify and eliminate the artifacts that are inadvertently introduced in the shock-blast profile that may affect the results. In this work, we examine the relationship between shock tube adjustable parameters (SAPs) and SWPs that can be used to control the blast profile; the results can be easily applied to many of the laboratory shock tubes. Further, exact replication of shock profile (magnitude and shape) can be related to field explosions and can be a standard in comparing results across different laboratories. 40 experiments are carried out by judiciously varying SAPs such as membrane thickness, breech length (66.68 to 1209.68 mm), measurement location, and type of driver gas (nitrogen, helium). The relationships between SAPs and the resulting shock-blast profiles are characterized. Finally, shock-blast profiles of a TNT explosion from ConWep software is compared with the profiles obtained from the tube.